Implementing Genre Based Approach to Improve Students’ Writing Skill at EFL Students In Indonesia - Yassin, Muhammad; Sood, Muhammad (Universitas Nurul Jadid, 2024)
This research is aimed at determining whether students’ writing skills can be improved through the implementation of a genre-based approach at SMK Awaludin Batu Ampar. This study is conducted based on the preliminary study which pointed out that most of the students lack of writing ability in the classroom instructional process. Being designed in classroom action research, it then adopts Kemmis and Mc Taggart model with two cycles in which each cycle comprises four phases; planning, acting, observing and reflecting. it is also a collaborative action research with the English teacher of the school in running the study. As the objective of the research is to improve students’ writing skill, the results indicate that Genre Based Approach is undeniably an effective strategy to resolve writing issues and increase students’ ability in writing a procedure text. The implementation of Genre Based Approach also encourages students to get involved actively in the learning process, promote self-awareness to gain better writing skill, and provoke students’ positive attitude in learning English.